Level of Adherence and Associated Factors to Option B+ PMTCT among HIV Positive Pregnant Women in Hadiya Zone, Southern Ethiopia - Lodebo, Terefe M.; Suloro, Juhar A. (Global Journal of Health Sciences, 2017)
Background: Option B+ is a test and treat strategy in which HIV+ pregnant women are initiated on antiretroviral therapy regardless of their immunologic status & clinical status and are maintained on treatment for life in an attempt to avert mother to child transmission of HIV and improve the survival of mothers, newborns and children. Adherence is the single most important modifiable factor to achieve the above outcome. Non-adherence to PMTCT drugs increases the risk of treatment failure, maternal HIV disease progression, and the potential development of drug-resistant virus. The study aimed to identify the level of adherence to the Option B+ PMTCT programme and factors associated with adherence among HIV positive pregnant women in the Hadiya zone, southern Ethiopia, 2016. Methods: A facility based cross-sectional study was conducted among 215 HIV-positive pregnant women in 2016. Data were collected using a structured interviewer-administered questionnaire. Data were entered into Epi-Data Statistical software version 3.1, and exported to SPSS version 21 for analysis. Descriptive statistics such as frequencies, proportions, and means were carried out. Multiple logistic regressions were used to estimate the effect sizes of factors associated with adherence to Option B+ PMTCT drugs. Results: The adherence level of respondents to option B+ PMTCT drugs was 83.7% (95 % CI: 78.3, 88.6). Mothers who were counseled on the side effects of ARV medications had 7.2 times higher odds (aOR 7.2, 95% CI 2.2, 22.8) of adhering to Option B+ PMTCT care and support as compared to those who were not counseled properly. Disclosing their HIV status to their partner was also positively associated with good adherence (aOR 3.09, 95% CI 1.04, 9.1). HIV positive pregnant women with good partner involvement in PMTCT care and support had 72% more likely to be adherent to option B+ PMTCT as compared to low (aOR 0.28; 95% CI: 0.06, 0.12). Conclusion: The adherence level of mothers towards PMTCT care and support was 83.7%. Proper counseling on the side effects of PMTCT drugs, care and support, HIV status disclosure to partners and Male partner involvement were significant predictors of adherence to PMTCT.